A fast algorithm for computing the Boys function - Beylkin, Gregory; Sharma, Sandeep (The Journal of chemical physics, 2021)
We present a new fast algorithm for computing the Boys function using a nonlinear approximation of the integrand via exponentials. The resulting algorithms evaluate the Boys function with real and complex valued arguments and are competitive with previously developed algorithms for the same purpose.